Jesus" identity in Matthew 16:13–20 and identity crisis among gospel preachers in Nigeria - Peters, Prince E. (HTS teologiese studies, 2024)
The Jesus’ question which was encased in his shadowy identity was both a fascinating and enigmatic phenomenon to people of Jesus time as well as people of today. The synoptic gospels presented the matter of Jesus identity in varying contexts; however, it is approached in this study from the context of Matthew. After receiving a brief answer of ‘who he is’ from Peter, Jesus mandates his disciples to keep the information to themselves. This mandate to secrecy shares certain characteristics with the Messianic secret in Mark, but differs in intentions. From the exegesis of the pericope in Matthew, Jesus’ refusal to let the public know about his personalities with his motive to keep away from ostentation and self-love. Such ostentation and self-love have been referred to in this study as identity crisis. This study argues from empirical evidence that many Nigerian pastors suffer from identity crisis. It therefore, challenges Nigerian contemporary preachers to emulate Jesus’ refusal of self-seeking and to shun hypocrisy and unnecessary publicity.Contribution: To reroute the Christian church in Nigeria, especially the pastors from ostentation and self-seeking publicity to a selfless and modest lifestyle modelled after Jesus’ own personality example according to Matthew 16:13–20.